Lingkungan dan Manajemen Perubahan dalam Organisasi - Nurhasanah Siregar; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Change is a series of actions that cannot be removed from an organization. The process of change is inevitable in any organization. The process of shifting from the current situation to the future state to improve an organization is known as organizational change. To prepare for and overcome the difficulties that will arise in the future, the organization will always go through transformation. Organizational change can start from inside or outside the company. The change can take the form of systematic change or structured change that must be carried out properly. Organizational leadership is needed to facilitate the course of change so that the organization can be improved in success. The success or failure of an organization greatly affects the success of that organization. Organizational change is not always well agreed upon because every change is met with rejection. The existence of organizational change can be a risk of organizational failure, so good management is needed so that the organization can develop.